Kebutuhan Model Valuasi Lingkungan Bagi Kegiatan Transportasi - Handajani, Mudjiastuti (MEDIA KOMUNIKASI TEKNIK SIPIL, 2007)
Apart from supporting to human life which is a part of positive impacts, transporation also contains negative impacts which does not only lead to local geographic scale of mainland, but also to the largesr one, including water and air environment, even atmosphere. When the negative impact comes to larger scale, macro decisions such policies supported by political issues should be intervented to minimize negative impacts and to develop a better transportation or a sustainable transportation in the future. It is an irony that most of professionals, technocrats, and scientiests related transportation in developing countries are still interested and focused in local issues of transportation phenomenon, model development for transportation planning and technical issues related to operational management analysis. Only a small group of them are interested in transportation impact studies for both local and larger area. It will be a rational justification to construct models to support decision making process in order to have a policy within line with sustainable environment which is not only useful for both local scale, but also larger scale (national and the earth).